Media training in Algeria between the necessities of upgrading academic research and the challenge to respond to development and democracy benefits - ALLAK, Rafika (Milev Journal of Research and Studies, 2019)
There is no doubt that the deep transformation witnessed by human life in the modern era has taken place at various levels , the media was not so much more aware of it , than it was the more fortunate element of the process of transformation and its main contributor . It has become one of the strategic proponents of building political , economic , social and cultural development projects , and successful development policies can not be established without effective reforms with well-defined media plans . The societal need for media research imposed a convergence of its results with community concerns through an integrated approach commensurate with current benefits , but the deepening of the media attention to the developmental problems and the democratic stakes , and the transition from stereotype transfer to active participation in all national construction plans and follow their cours .